PROMATCH: A TECHNOLOGICAL SOLUTION TO FACILITATE SERVICE HIRING AND PROMOTE DIGITAL INCLUSION FOR FREELANCE PROFESSIONALS (CIPEEX, 2025)
Nowadays, hiring specialized services such as electricians, plumbers, and cleaners stillrepresents a challenge for many consumers. The lack of qualified professionals or a reliablechannel to find these service providers creates uncertainty, both in terms of quality and safety.Additionally, many self-employed workers face difficulties in positioning themselves in themarket and gaining the visibility necessary to offer their services consistently and sustainably.This scenario highlights the urgent need for a solution that efficiently connects clients andservice providers, ensuring safety, agility, and quality.Promatch emerges as an innovative response to this demand, offering a digital platform thatfacilitates the connection between specialized professionals and clients. By leveragingtechnology to simplify the hiring process, Promatch transforms the service market, removingbarriers that hinder access to qualified professionals. The platform provides a practical andefficient solution, enabling clients to quickly find reliable service providers, while self-employedprofessionals expand their visibility and clientele.One of Promatch's key innovations is its continuous evaluation system, which allows users toassess the performance of service providers. This mechanism not only ensures the quality ofthe work performed but also promotes the constant improvement of the services offered. Therigorous professional registration process, combined with user evaluations, ensures thatclients have access to a trustworthy network of qualified workers.In addition to solving the problem of the difficulty in hiring services, Promatch plays a crucialrole in the social and digital inclusion of self-employed professionals, many of whom lack thevisibility necessary to attract new clients. The platform enables these workers to have a directchannel to offer their services, generating new income opportunities and contributing to localeconomic growth.Thus, Promatch is not just a technological solution to facilitate the hiring of specializedservices; it also promotes social inclusion, encourages professionalization, and ensures ahigh-quality experience for clients. With its innovative approach, the platform transforms themarket, creating a safe and efficient environment for both professionals and consumers.
Keywords: service mediation; continuous evaluation; digital inclusion